Soaking beans for 12 h reduces split percent and cooking time regardless of type of water used for cooking - Munthali, Justice; Nkhata, Smith G.; Masamba, Kingsley; Mguntha, Timothy; Fungo, Robert; Chirwa, Rowland (Elsevier, 2022)
Beans are one of the most important cheap source of protein in developing countries. However, their utilisation in the diets of many people remains limited due to long cooking time, among others. Therefore, it is imperative to identify ways to enhance utilisation of beans. The aim of the current study was to assess the effects of soaking and cooking in different types of water (tap, borehole, acidulated- 1.0 percent citric acid and soda- 0.2 percent sodium bicarbonate) on cooking time (CT), split percentage (SP) and total soluble solids (TSS) in broth of different va rieties of beans. Results show that soaking significantly reduced CT across eight varieties from an average CT of 109.5–84.6 min in tap water, 109.5–85.2 min in borehole water, 115.9–92.7 min in acidulated water and 82.0–51.2 min in soda water representing 22.7%, 22.1%, 20.0% and 37.6% reduction in CT, respectively. Soaking generally decreased SP and varietal differences were observed suggesting beans are less likely to break when soaking precede cooking. Although cooking in soda water significantly reduced CT, unfortunately, it increased SP. Acidulated water extended CT but reduced SP in almost all varieties. Soaking generally decreased TSS in broth from 7.0 to 6.7% in tap water, 6.1–5.8% in borehole water and 11.3–7.7% in soda water while it increased TSS in acidulated water from 18.2 to 20.6% across all the eight varieties which suggest reduction in leaching out of bean solids into cooking water which is consistent with reduced SP of soaked beans. While use of soda water reduced cooking time and therefore saved time and energy, its effect of increasing split percent may not be appealing to some consumers. This study has demonstrated that bean soaking significantly reduced cooking time and split percent and these can also be affected by type of cooking water.